Efectividad de los cuentos como herramienta terapéutica en el trabajo con el autoconcepto en niñas y niños víctimas de violencia psicológica en edades comprendidas de 8 a 10 años del sector La Marín del Programa Acción Guambras - Hinojosa Alcocer, María Cristina (2018)
By means of the work the topic of how effective sound tackled the stories as therapeutic tool in the work with the autoconcept, since one tries to demonstrate the effect and changes that it causes in every participant, all this will realize by means of the indicators as: its positive narrative, corporal expression, empathy with the activity, conducts and positive behaviors, the control of the frustration and impulses, change of thoughts of uselessness, projection total and introyection, implantation of the confidence, safety, comprehension of fears and worries. In addition, through the stories the participants were incorporating resources such as self-confidence, valorization, the security that was observed when expressing their thoughts and feelings in front of the group, noting that they were shedding their fears and anguish. Another form that showed the effectiveness of the stories as therapeutic tool in the work with the autoconcept was with a quantitative variable since there was application the Test of self-esteem of Rosenberg before beginning the work and later at the end of the work, demonstrating favorable results. One worked with girls and children who live together with the psychological violence, which there is to affect in its autoconcept and in the inappropriate forms of conduct of the children.